2020
DOI: 10.1186/s11671-020-03399-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Specificity of HEK293T Extracellular Vesicle Uptake using Imaging Flow Cytometry

Abstract: Extracellular vesicles (EVs) are nanosized lipid bilayer-bound vesicles that are naturally secreted from most cell types as a communication mechanism to deliver proteins, lipids, and genetic material. Despite the therapeutic potential of EVs, there is limited information on EV uptake kinetics and specificity. Here, we optimized an imaging flow cytometry (IFC)-based platform to quantitatively assess dose, time, and recipient cell specificity effects on human embryonic kidney cell (HEK293T) EV internalization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 60 publications
(127 reference statements)
1
55
0
Order By: Relevance
“…Despite advances in our understanding of the molecular mechanisms underlying EV internalization, the long-standing question of EV uptake specificity remains to be comprehensively addressed in the field. While studies have indicated the prevalence of EV uptake into any cell type tested [73,80], results from other studies demonstrated that EV uptake is a highly specific process in which the recipient cells and EVs would require the 'right' type of surface receptors and ligands for the coordinated protein-protein interactions [43,50,[80][81][82][83][84]. For example, the fusion of anti-epidermal growth factor receptor (EGFR) nanobodies to glycosylphosphatidylinositol (GPI) anchor signal peptides on the EV surface was sufficient to alter their cell targeting behavior and promote efficient binding to tumor cells that are dependent on EGFR density [81].…”
Section: Ev Transportation and Uptake: Specific Or Random?mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite advances in our understanding of the molecular mechanisms underlying EV internalization, the long-standing question of EV uptake specificity remains to be comprehensively addressed in the field. While studies have indicated the prevalence of EV uptake into any cell type tested [73,80], results from other studies demonstrated that EV uptake is a highly specific process in which the recipient cells and EVs would require the 'right' type of surface receptors and ligands for the coordinated protein-protein interactions [43,50,[80][81][82][83][84]. For example, the fusion of anti-epidermal growth factor receptor (EGFR) nanobodies to glycosylphosphatidylinositol (GPI) anchor signal peptides on the EV surface was sufficient to alter their cell targeting behavior and promote efficient binding to tumor cells that are dependent on EGFR density [81].…”
Section: Ev Transportation and Uptake: Specific Or Random?mentioning
confidence: 99%
“…In addition, CD63-positive EVs were specifically bound to neuronal and glial cells, whereas CD63-negative EVs targeted only to the dendritic cells of neurons [82]. Recent evidence also indicated that the transfer of secreted exosomes is selective to the cell type of origin i.e., exosomes are preferentially taken up by cell types where they were originally secreted from [83,84]. Furthermore, EV uptake can also be affected by factors such as metabolic status of the recipient cells, and attributes including the types and characteristics of secreted EVs [47,84].…”
Section: Ev Transportation and Uptake: Specific Or Random?mentioning
confidence: 99%
See 2 more Smart Citations
“…Image flow cytometry has been used for the detection of exosome and vesicle transference. For this study, Jurgielewicz et al transfected HEK293T cells with a plasmid coding for the CD63‐eGFP fusion protein [113]. CD63, an exosomal marker present in exosome membranes, fused with eGFP can be easily tracked by flow cytometry.…”
Section: Cytometry Techniques For Studying Gbm‐mscs Interactions In Vmentioning
confidence: 99%